A cooperative (or coordinated) multi-agency response to enhance the effectiveness of aerial bushfire suppression operations. (July 2021) - Shahparvari, Shahrooz; Bodaghi, Behrooz; Roozbeh, Iman; Mohammadi, Mahsa; Soleimani, Hamed; Chhetri, Prem
Abstract: An effective and efficient suppression of a bushfire is predicated on synchronised collaborative planning, information sharing, scheduling and tasks coordination between multiple agencies. This paper aims to develop a bushfire suppression optimisation model, which minimises the completion times and total costs within resource constraints. An algorithm is developed to tackle the highly complex operational response to bushfire suppression via aerial firefighting. A real case study of 2009 Black Saturday bushfires in Victoria is used to create the situational context and to derive model parameters. Three scenarios are designed to incorporate time and resource constraints to reflect a highly uncertain and dynamic situated bushfire environment. This study has generated bushfire suppression plans in emergency situations by improving resource utilisation efficiency and time scheduling. In the baseline scenario, the model indicates the ability of fire agencies to complete all operational activities, but in the scenarios where resource shortage and time limitations exist, the cost of unmet demands fell slightly. The outcomes of the proposed approach will help to enhance multi-agencies coordination in fire suppression evacuation plans to improve operational response and maximise geographic coverage of service delivery.